Penerapan Arsitektur Islam pada Rencana Pembangunan Pusat Kebudayaan Islam di Bulukumba - Wahidin, Rahmat; Marwati, Marwati; Sam, Mukhlishah (TIMPALAJA : Architecture Student Journals, 2024)
As one of the districts that is concerned with religious activities, namely Bulukumba, a forum is needed for the community or the government to carry out these activities in the form of an Islamic Cultural Center which accommodates the various needs of community activities. The design of the Islamic Cultural Center is a facility with supporting facilities that support educational, social, health, economic activities, and a center for preaching the spread of Islam. The design of the Islamic Cultural Center in Bulukumba Regency, applies an Islamic architectural approach that is in line with the building’s functions based on basic Islamic principles, as contained in the Al-Qur’an and Al-Hadith. Then it is poured in the form of architectural design in accordance with architectural disciplines which are expected to be able to foster community interest and enthusiasm in carrying out Islamic activities, especially in the people of Bulukumba Regency.